Status Of the Community Based Monitoring at Sub Centers in Maharashtra - Kulkarni, Ashok P; Doke, Prakash P (National Journal of Community Medicine, 2013)
Introduction: The system of Community Based Monitoring (CBM) was implemented as a project in five districts of the State of Maharashtra. In each district three blocks and in each block 3 Primary Health Centers were included. Objectives: We conducted the study to assess the implementation process and effects of the implementation after three years of execution. Material and Methods: The study was carried out with the help of Community Medicine Departments from nearby Medical Colleges. First we selected 45 sub centers from the project implementing areas and equal numbers were selected for comparison from three blocks from Non-CBM implementing area. Results: Only 44.44% ANMs were trained in CBM process. We did not find any difference between the CBM and Non-CBM group of sub centers in the assessment of sub centers, ANMs, services provided and expenditure incurred. Difference was observed in displaying of village wise health days calendar and registration of ante natal women. Conclusions: Small proportion of ANM had undergone the training and secondly the duration of the training was not uniform. This may be the reason for lack of difference in the two groups.